PERANCANGAN PROTOTYPE MONITORING DAN KONTROL UNTUK DETEKSI KUALITAS TELUR AYAM PADA PETERNAKAN FADILLAH JAYA SUMBAWA BERBASIS INTERNET OF THINGS (IOT) - Sedri sella; Ekastini; Nora Dery Sofya (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2025)
Egg quality inspection before distribution is crucial to ensure edibility and prevent complaints from retailers or distributors. Fadillah Jaya Sumbawa (FJS) Poultry Farm still uses a manual method for this process, which takes a long time and risks data recording errors. This study aims to design a monitoring and control prototype based on the Internet of Things (IoT) to detect egg quality. The system utilizes a light-dependent resistor (LDR) sensor to analyze the intensity of light passing through the eggshell and transmits the data to an IoT platform for easier monitoring. Additionally, a control mechanism is integrated to support the inspection process. The research method follows the Software Development Life Cycle (SDLC) approach using the prototype model. The results indicate that the designed prototype can assist poultry farms in reducing data recording errors and minimizing complaints from retailers or distributors.